Status of comprehensive geriatric assessment in hospital settings: a cross-sectional survey - Lyu, Hong; Dong, Yan; Chen, Rui; Zeng, Yan; Liu, Jia; Song, Xinhong; Wang, Huihui; Xing, Liqun; Zhang, Xin; Wang, Ying (Frontiers in Medicine, 2025)
BackgroundThe Comprehensive Geriatric Assessment (CGA) serves as a crucial multidimensional instrument for optimizing care within aging populations. Despite its demonstrated benefits, there remain significant implementation gaps in China, particularly within Shandong Province. This study examines the current status, facilitators, and barriers to CGA implementation from the perspective of geriatric nurse specialists (GNS).MethodsA cross-sectional survey was administered to 200 GNS trained by the Shandong Nursing Association between 2018 and 2022. Data collection was conducted using a validated questionnaire grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Statistical analyses were performed using chi-square tests and odds ratio (OR), with significance set at p < 0.05.ResultsCGA implementation was observed in only 50.50% of medical institutions. Key facilitators included Hospital level (secondary/tertiary: OR = 5.30, 95% CI: 2.29–12.25), Staff training (OR = 5.39, 95% CI: 1.75–16.56), Dedicated CGA personnel (OR = 3.41, 95% CI: 1.86–6.24), Interventions based on CGA results (OR = 7.34, 95% CI: 2.44–22.12). Unexpectedly, GNS certification (OR = 0.44, 95% CI: 0.21–0.91) appeared to impede implementation. The primary barriers identified were the time-intensive nature of the process (64%), insufficient involvement of multidisciplinary teams (62%), and the absence of insurance reimbursement (48%).ConclusionThe adoption of CGA in Shandong remains below optimal levels. To enhance implementation, it is imperative to develop policy-driven strategies that include integrating CGA into insurance reimbursement frameworks, standardizing digital workflows, expanding multidisciplinary teams, and addressing workforce shortages through targeted training initiatives.